Urtica dioica inhibits cell growth and induces apoptosis by targeting Ornithine decarboxylase and Adenosine deaminase as key regulatory enzymes in adenosine and polyamines homeostasis in human breast cancer cell lines - Fattahi, Sadegh; Ghadami, Elham; Asouri, Mohsen; Motevalizadeh Ardekanid, Ali; Akhavan-Niaki, Haleh (Cellular and Molecular Biology, 2018)
Breast cancer is a heterogeneous and multifactorial disease with variable disease progression risk, and treatment response. Urtica dioica is a traditional herb used as an adjuvant therapeutic agent in cancer. In the present study, we have evaluated the effects of the aqueous extract of Urtica dioica on Adenosine deaminase (ADA) and Ornithine decarboxylase (ODC1) gene expression in MCF-7, MDA-MB-231, two breast cancer cell lines being estrogen receptor positive and estrogen receptor negative, respectively. Cell lines were cultured in suitable media. After 24 h, different concentrations of the extract were added and after 72 h, ADA and ODC1 gene expression as well as BCL2 and BAX apoptotic genes were assessed by Taqman real time PCR assay. Cells viability was assessed by MTT assay, and apoptosis was also evaluated at cellular level. The intra and extracellular levels of ODC1 and ADA enzymes were evaluated by ELISA. Results showed differential expression of ADA and ODC1 genes in cancer cell lines. In MCF-7 cell line, the expression level of ADA was upregulated in a dose-dependent manner but its expression did not change in MDA-MB cell line. ODC1 expression was increased in both examined cell lines. Also, increased level of the apoptotic BAX/BCL-2 ratio was detected in MCF-7 cells. These results demonstrated that Urtica dioica induces apoptosis in breast cancer cells by influencing ODC1 and ADA genes expression, and estrogen receptors. The different responses observed with these cell lines could be due to the interaction of Urtica dioica as a phytoestrogen with the estrogen receptor.